Peran Subbagian Advokasi Dan Dokumentasi Hukum Sekertariat Jenderal Dalam Penyelesaian Sengketa MPR RI - Harahap, Viviyen Jensifa; Hafizd, Jefik Zulfikar (Hutanasyah : Jurnal Hukum Tata Negara, 2023)
This journal is motivated by the idea that the role of advocacy in dispute resolution is needed as an advocate who acts as an advisor or defender of cases in court. As one of the people's representative bodies or the legislature of the People's Consultative Assembly consisting of members of the People's Representative Council and Regional Representative Councils elected through general elections, it is certainly not spared from the many disputes or cases submitted by the community who are increasingly critical of existing policies to the court. In dispute resolution, the People's Consultative Assembly requires the role of the legal section, especially the advocacy subdivision and legal documentation to carry out its duties and functions as an advocate. Which plays a role in providing Exepsies, Duplik, Replications, Submitting evidence against claims by legal entities in court to obtain a decision with permanent legal force.